2006
DOI: 10.1097/01.mlg.0000230479.39551.4a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Compatibility and Safety of the SOUNDTEC Direct System

Abstract: When considering MRI of implantable ferromagnetic hearing devices, issues related to mechanical forces, implant heating, current induction, implant demagnetization, image degradation, and acoustic trauma must be considered. The SOUNDTEC Direct System is both MRI-compatible and safe in a 0.3-Tesla open MRI environment when a modified protocol is used. Degradation of the head MRI image may impair visualization of the ipsilateral temporal bone and adjacent structures within a 2.5- to 4.3-cm radius of the implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…We randomly positioned the TBs in the MRI field so that the magnetic field affected the FMTs in different ways and extents. Based on the conclusions and suggestions to surgeons by Dyer et al (2006), it can be assumed that by positioning the FMT in the direction of the field strength, the positional force can be lowered, and, therefore, the risk of a positional change is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…We randomly positioned the TBs in the MRI field so that the magnetic field affected the FMTs in different ways and extents. Based on the conclusions and suggestions to surgeons by Dyer et al (2006), it can be assumed that by positioning the FMT in the direction of the field strength, the positional force can be lowered, and, therefore, the risk of a positional change is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dyer and colleagues 12 more recently reported that patients with the SOUNDTEC device may safely undergo low-strength MRI. This study showed no patient-or device-related complications in 11 patients with the SOUNDTEC device who underwent a total of 12 head, 1 shoulder, and 3 lumbar MRIs at a strength of 0.3 T. 12 To minimize MRI-related risks, Dyer and colleagues 12 recommended a protocol whereby the patient was positioned so that the implant and MRI static fields were oriented parallel and the head was placed in a lateral position (to minimize implant torque). Furthermore, the use of a fast spin echo sequence may reduce implant artifact and image degradation in the region of the implant.…”
Section: Precautions With the Maxum Systemmentioning
confidence: 98%
“…There are several ways in which the MRI scanner and the microtransponder might interact: for example, the magnetic forces or the radio waves involved in each technology may interfere with one another. Deterioration of image quality due to susceptibility of artifacts, movement of microchips, and the heating of the transponder is documented . The technical components of the transponder could be damaged by heating.…”
Section: Introductionmentioning
confidence: 99%